A phase 1 healthy male volunteer single escalating dose study of the pharmacokinetics and pharmacodynamics of risdiplam (RG7916, RO7034067), a SMN2 splicing modifier. Issue 1 (16th November 2018) - Sturm, Stefan; Günther, Andreas; Jaber, Birgit; Jordan, Paul; Al Kotbi, Nada; Parkar, Nikhat; Cleary, Yumi; Frances, Nicolas; Bergauer, Tobias; Heinig, Katja; Kletzl, Heidemarie; Marquet, Anne; et al.
Abstract : Aims: Risdiplam (RG7916, RO7034067) is an orally administered, centrally and peripherally distributed, survival of motor neuron 2 ( SMN2 ) mRNA splicing modifier for the treatment of spinal muscular atrophy (SMA). The objectives of this entry‐into‐human study were to assess the safety, tolerability, pharmacokinetics (PK) and pharmacodynamics of risdiplam, and the effect of the strong CYP3A inhibitor itraconazole on the PK of risdiplam in healthy male volunteers. Methods: Part 1 had a randomized, double‐blind, adaptive design with 25 subjects receiving single ascending oral doses of risdiplam (ranging from 0.6–18.0 mg, n  = 18) or placebo ( n  = 7). A Bayesian framework was applied to estimate risdiplam's effect on SMN2 mRNA. The effect of multiple doses of itraconazole on the PK of risdiplam was also assessed using a two‐period cross‐over design ( n  = 8). Results: Risdiplam in the fasted or fed state was well tolerated. Risdiplam exhibited linear PK over the dose range with a multi‐phasic decline with a mean terminal half‐life of 40–69 h. Food had no relevant effect, and itraconazole had only a minor effect on plasma PK indicating a low fraction of risdiplam metabolized by CYP3A. The highest tested dose of 18.0 mg risdiplam led to approximately 41% (95% confidence interval 27–55%) of the estimated maximum increase in SMN2 mRNA. Conclusions: Risdiplam was well tolerated and proof of mechanism was demonstrated by the intended shift in SMN2 splicing towards full‐length SMN2 mRNA. Based on these data, Phase 2/3 studies of risdiplam in patients with SMA are now ongoing. Abstract :